Makna Nilai Silas dalam Perkawinan Katolik Sunda - Alfrianto, Kristoforus (Perspektif, 2020)
The article highlights one of the local wisdoms of the ethnic Sunda, namely Silih Asih, Silih Asah, Silih Asuh (SILAS). Silih Asih is interpreted as loving one another from the depth of one’s heart. Silih Asah means a mutual enhancementfor improving the qualities human life. While Silih Asuh is regarded as a mutual education among members of the community for a harmonious life. With such noble values, the Sundanese have been expected to build up their families accordingly. In so-doing the people could realize a harmonious life in their society. The Sundanese in general, as well as the Catholics in particular, have been so familiar with the Silas values. The writer then argues that the Catholics are highly expected to internalize the values in their marital life and as part of their being Sundanese.